Studi Kelayakan Pompanisasi Sebagai Alternatif Pengairan Sawah untuk Meningkatkan Produktivitas Padi di Desa Belang Turi - Jandu, Inosensius Harmin; Lorensius Santu; Yosef Kurniawan Ukar; Yostones Hardi (Lembaga Pengembangan Kinerja Dosen, 2025)
Farmers are grappling with drought challenges that jeopardize rice production. To address this, the government is promoting the use of water pumps and the construction of reservoirs. However, reservoir development comes with specific stipulations, such as the land used needing to be owned by the village or government. Climate change poses a significant challenge to Indonesia's agricultural sector. The pump irrigation program has emerged as a crucial solution for water scarcity in farmlands. This research was conducted in Belangturi Village, Ruteng District, Manggarai Regency, chosen purposively due to its status as a key rice paddy development area. The study took place from December 2023 to April 2024, employing simple random sampling. Data indicates there are 40 active rice paddy farmers in Belang Turi Village. An economic analysis forecasts substantial benefits from this program, including a 20-30% increase in rice production, an improved cropping index, crop diversification, and a 40-60% rise in farmer income. The financial analysis yields highly positive results: an NPV of IDR 450,000,000, an IRR of 18%, a Payback Period of 4.5 years, and a BCR of 1.75, all strongly indicating a highly feasible investment. From a social standpoint, pump irrigation is desperately needed and enthusiastically supported by the community. It's perceived as vital for overcoming critical water shortages, enhancing welfare, and improving access to education and healthcare. Therefore, implementing this pump irrigation system is highly recommended as a comprehensive solution for sustainable agricultural development in Belang Turi Village.